Adolescent's Health Perceptions of E-Cigarettes: A Systematic Review - Sharma, A.; McCausland, K.; Jancey, Jonine (2021)
Context: E-cigarette use is increasing among adolescents, particularly in high-income countries. This review examines the health perceptions of E-cigarettes among adolescents (aged 12–17 years) residing in the U.S., United Kingdom, Canada, Australia, and New Zealand and their sources of E-cigarette information.